IITA: Food crops research for Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
IITA, the International Institute of Tropical Agriculture, was established in 1976 as the first major African link in an integrated network of international research and training centres located throughout the developing regions of the world. Its...